Awareness and Clinical Practices on Implant Abutment Cleaning in Türkiye - Habibe Öztürk Ulusoy; Rüveyda İrem Şentürk; Süeda Kılıç; Şafak Çiçek (Acta Odontologica Turcica, 2026)
OBJECTIVE: There is no standard protocol for abutment cleaning before the final abutment–implant connection to minimize contamination-related risks that can be applied in the clinic. This research aims to determine whether Turkish dentists use any cleaning, disinfection, and/or sterilization procedures before connecting customized abutments to the implant and, if so, which procedures they apply. METHODS: This study was conducted between 15.12.2022 and 15.06.2023. A link to the survey consisting of four questions was sent to the dentists via e-mail. The survey was sent to dentists registered with the Turkish Dental Association and affiliated with Dentistry Faculties in Türkiye. Frequency analysis was executed for all responses. RESULTS: A total of 500 dentists, 148 (29.8%) from universities, and 348 (70.2%) from private institutions participated in the study. The survey findings showed that 96 respondents (19.4%) did not follow cleaning, disinfecting, or sterilizing protocols for abutments before the abutment and implant were attached, while the remaining 400 (80.6%) employed at least one of the methods for disinfection and/or sterilization. Of those who followed a cleaning protocol, 178 (44.5%) performed disinfection with formaldehyde, chlorhexidine, ethanol, H2O2, and alcohol, and 176 (44%) performed sterilization with dry heat and an autoclave. Only 44 (11%) respondents preferred to use disinfection and sterilization methods in combination. CONCLUSION: Although the clinical practices of clinicians in Türkiye regarding cleaning abutments before the final implant-abutment connection have a significant heterogeneity, their awareness of this issue is very high.